Process simulation and assessment of a back-up condensate stabilization unit - Rahmanian, N. (Elsevier B.V., 2015)
A simulation was conducted using Aspen HYSYSÂ® software for an industrial scale condensate stabilization unit and the results of the product composition from the simulation were compared with the plant data. The results were also compared to the results obtained using PRO/II software. The results show that the simulation is in good agreement with the plant data, especially for medium range hydrocarbons. For hydrocarbons lighter than C5, the simulation results over predict the plant data while for hydrocarbons heavier than C9 this trend is reversed. The influences of steam temperature and pressure, as well as feed conditions (flow rate, temperature and pressure) for the product specification (RVP and sulphur content) were also investigated. It was reported that the operating conditions gave rise to the production of off-specification condensate and it was also found that the unit could be utilized within 40-110 of its normal throughput without altering equipment sizing and by the operating parameters. Â© 2015 Published by Elsevier B.V.